A digital map of folk songs from the collection of Adolf Dygacz - Mateusz Napiórkowski (Journal of Folklore and Popular Culture, 2021)
Adolf Dygacz. Historia muzycznej podróży (Adolf Dygacz: The history of the musical journey). Website created by Agata Krajewska: https://adolfdygacz.pl/